Aortic Calcification - Jayalath, R.W.; Mangan, S.H.; Golledge, J. (European journal of vascular and endovascular surgery, 2005)
Vascular calcification is a complicating factor observed in advanced atherosclerosis. This review summarises the present knowledge regarding abdominal aortic calcification. Literature review. A literature review was carried using MEDLINE and PUBMED with the search terms ‘abdominal’, ‘aortic’ and ‘calcification’. Articles were assessed for data regarding mechanisms, measurement, risk factors and outcomes of aortic calcification. Thirty relevant studies were identified. These demonstrated a positive correlation between abdominal aortic calcification and the following factors: older age, hypertension, and smoking. Further studies are required to critically assess other risk factors such as gender, diabetes mellitus and renal failure. Calcification of the abdominal aorta is associated with an increased risk of mortality, coronary heart disease and stroke. Aortic calcification predicts an increased incidence of cardiovascular events, however, the reasons for this association requires further investigation. Accurate measurement of aortic calcification is likely to be increasingly used to determine the risk of cardiovascular events.